Europe and Central Asia Balancing Act : Cutting Subsidies, Protecting Affordability, and Investing in the Energy Sector in Eastern Europe and Central Asia Region - World Bank (Washington, DC, 2012)
The cost of energy in Eastern Europe and Central Asia, as elsewhere, is an important policy issue, as shown by the concerns for energy affordability during the past harsh winter. Governments try to moderate the burden of energy expenditures that is experienced by households through subsidies to the energy providers, so that households pay tariffs below the cost recovery level for the energy they use. These subsidies result in significant pressures on government budgets when international prices rise. They also provide perverse incentives for the overconsumption of energy as households do not pay the true cost of energy, and therefore, have fewer incentives to save or to invest in energy efficiency. Balancing competing claims-fiscal and environmental concerns which would push for raising energy tariffs on the one hand and affordability and political economy concerns which push for keeping tariffs artificially low on the other-is a task that policy makers in the region are increasingly unable to put off. Addressing this issue is all the more pressing as the ongoing crisis continues to add stress to government budgets, and that international energy prices remain high. This is the first report to assess, at the micro level for the whole region, the distributional impact of raising energy tariffs to cost recovery levels and to simulate policy options to cushion these impacts.